Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Using DeMorgan's Law, write an expression for the complement of F if

F(w, x, y, z) = xyz'(y'z + x)' + (w'yz + x')

F' = (xyz'(y'z + x)' + (w'yz + x'))'

= (xyz'(y'z + x)')' * (w'yz + x')'

= ( (xyz')' + (y'z + x) ) * ( (w'yz)' * x )

= ( ( (xy)' + z ) + (y'z + x) ) * ( ( w + (yz)' ) * x )

= ( ( (x' + y') + z ) + (y'z + x) ) * ( ( w + ( y' + z') ) * x )

= x' + y' + z + (y'z + x)(w + y' + z')x

where this is the appropriate solution given.

But now if we first start like this:

F = xyz'(y'z + x)' + (w'yz + x')

= xyz'((y'z)'x') + (w'yz + x')

= xyz'(((y')' + z')x') + (w'yz + x')

= xyz'((y + z')x') + (w'yz + x')

= xyz'(x'y + x'z') + (w'yz + x')

= xy(x'yz' + x'z') + (w'yz + x')

= x(x'yz' + x'yz') + (w'yz + x')

= xx'yz' + xx'yz' + (w'yz + x')

= xx'yz' + (w'yz + x')

= 0(yz') + (w'yz + x')

F'= (w'yz + x')'

= (w + y' + z')x

and given that

x' + y' + z + ((y'z + x)((w + y' + z')x))

= ((x' + y' + z) + (y'z + x))((x' + y' + z) + ((w + y' + z')x))

= (1 + y' + z + y'z) * ((x' + y' + z) + ((w + y' + z')x))

= (x' + y' + z) + ((w + y' + z')x)

= ((x' + y' + z) + (w + y' + z')) * ((x' + y' + z) + x)

= x' + y' + z + w + y' + z'

= 1

but

(w + y' + z')x != 1

then what have I done that causes the inequality???

share|improve this question
    
When you go from $(w'yz+x')$ to $(w+y'+z')x$ (just before "and given that"), aren't you missing a negation? $$(w'yz+x') = \Bigl( (w'yz)'x\Bigr)' = \Bigl((w+y'+z')x\Bigr)'.$$ –  Arturo Magidin Apr 20 '11 at 20:59
    
I forgot to make it F' = and also take the complement while I was copying it over, yes. I edited it in thank you! –  Xittenn Apr 20 '11 at 21:20
    
@PrettyFlower: Now your solution is correct, and your only problem seems to be that you were given an incorrect "appropriate solution" :-) –  joriki Apr 20 '11 at 21:25
    
I hadn't written in all the steps properly. Given your correction(edited in), which I omitted in my original solution, I still get the same final answer. :/ –  Xittenn Apr 20 '11 at 21:38
    
Very sorry about my attention to detail on this post! –  Xittenn Apr 20 '11 at 21:43

1 Answer 1

up vote 2 down vote accepted

Fortunately it is not within your powers to cause inequalities :-)

There are mistakes both in what you call the "appropriate solution" and in your alternative solution. That the appropriate solution can't be right follows from the fact that, as you correctly deduced, it reduces to $F'\equiv1$, whereas $F\not\equiv0$.

The mistake in the derivation of the appropriate solution is in the first step,

$$(xyz'(y'z + x)' + (w'yz + x'))'= ((xyz')') + ((y'z + x)(w'yz + x')')\;,$$

which should be

$$(xyz'(y'z + x)' + (w'yz + x'))'= ((xyz'(y'z + x)')'(w'yz + x')'\;.$$

The mistake in your alternative solution is the last step,

$$(w'yz + x')= (w + y' + z')x\;,$$

which would be a correct application of De Morgan's law if the left-hand side had been complemented.

share|improve this answer
    
(as per the last) or the right hand side were complemented. –  Arturo Magidin Apr 20 '11 at 21:02
    
@Arturo: True :-) –  joriki Apr 20 '11 at 21:03
    
This and your comments answer the question, thank you! –  Xittenn Apr 20 '11 at 21:57
    
@PrettyFlower: You're welcome! By the way, one automatically gets notified of comments to one's own answer, but if you want someone to be notified of a response to other comments (as above for our exchange of comments to the question), you need to ping them using the @username syntax; otherwise you depend on them coming back to check for a response. –  joriki Apr 20 '11 at 22:04
    
thanks you for the heads up! –  Xittenn Apr 20 '11 at 22:20

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.